ENHANCING OIL PALM YIELDS THROUGH THE INTEGRATION OF SHARIA ECONOMICS AND AGROECOLOGY: A CASE STUDY OF MEKAR INDAH JAYA FARMER GROUP - Hidayat, Sarif; Muslimin, A.; Agus Mushodiq, M.; Ligery, Finny; Yusuf, M. (Jurnal Dinamika Ekonomi Syariah, 2025)
This study aims to analyze strategies for improving oil palm agricultural yields based on the perspective of Sharia economics and agroecology within the Mekar Indah Jaya Farmer Group. The method used is a qualitative approach through case studies, observation, interviews, and documentation. The results show that the application of the principles of tawhid and khilafah, along with agroecological practices, can enhance harvest yields, environmental sustainability, and social welfare. Strategies such as the use of organic fertilizers, muzara’ah contracts, and spiritual activities like communal prayers and harvest almsgiving are key determining factors. This model demonstrates the effectiveness of integrating Sharia values and environmental preservation in sustainable oil palm farming.